EVALUATING THE EFFECTIVENESS OF POINT-OF-CARE TESTING BY MEDICAL LABORATORY TECHNICIANS IN REDUCING TURNAROUND TIME AND ENHANCING CLINICAL DECISION-MAKING IN THE EMERGENCY DEPARTMENT - Ahoud Faisal Almutairi, Ali Mohammed Qushaish , Ghader Hamdan Alanazi , Mafareh Mana Alonazi , Mahfouz Alwy Ahmad Sharahili , Salem Fahad Alanazi (Chelonian Research Foundation, 2022)
Point-of-care testing (POCT) has emerged as a valuable tool in emergency departments (EDs) to provide rapid diagnostic results and improve patient care. This study aims to evaluate the effectiveness of POCT performed by medical laboratory technicians in reducing turnaround time (TAT) and enhancing clinical decision-making in the ED. A prospective observational study was conducted in the ED of King Abdulaziz Medical City in Riyadh, Saudi Arabia, from January to December 2022. The study included 1,500 adult patients who underwent POCT for common ED tests, such as troponin, blood glucose, and electrolytes. The primary outcomes were the TAT for POCT compared to central laboratory testing and the impact of POCT on clinical decision-making, as assessed by the time to diagnosis, treatment initiation, and disposition. Secondary outcomes included the agreement between POCT and central laboratory results and the satisfaction of ED staff with POCT. The results showed that POCT significantly reduced the median TAT compared to central laboratory testing (15 minutes vs. 45 minutes, p<0.001). POCT also led to faster diagnosis (30 minutes vs. 60 minutes, p<0.001), earlier treatment initiation (45 minutes vs. 75 minutes, p<0.001), and shorter time to disposition (90 minutes vs. 120 minutes, p<0.001). The agreement between POCT and central laboratory results was high (kappa=0.95). ED staff reported high satisfaction with POCT (92%). The findings suggest that POCT performed by medical laboratory technicians can significantly reduce TAT and enhance clinical decision-making in the ED, leading to improved patient care and staff satisfaction. The study highlights the importance of integrating POCT into ED workflow and ensuring adequate training and quality control measures for medical laboratory technicians. Keywords: point-of-care testing, medical laboratory technicians, turnaround time, clinical decision-making, emergency department